Extracellular biosynthesis of gadolinium oxide (Gd2O3) nanoparticles, their biodistribution and bioconjugation with the chemically modified anticancer drug taxol - Khan, Shadab Ali; Gambhir, Sanjay; Ahmad, Absar (Beilstein Journal of Nanotechnology, 2014)
As a part of our programme to develop nanobioconjugates for the treatment of cancer, we first synthesized extracellular, protein-capped, highly stable and well-dispersed gadolinium oxide (Gd2O3) nanoparticles by using thermophilic fungus Humicola sp. The biodistribution of the nanoparticles in rats was checked by radiolabelling with Tc-99m. Finally, these nanoparticles were bioconjugated with the chemically modified anticancer drug taxol with the aim of characterizing the role of this bioconjugate in the treatment of cancer. The biosynthesized Gd2O3 nanoparticles were characterized by UV-vis spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoemission spectroscopy (XPS). The Gd2O3-taxol bioconjugate was confirmed by UV-vis spectroscopy and fluorescence microscopy and was purified by using high performance liquid chromatography (HPLC).
Keywords: bioconjugation; biodistribution; gadolinium oxide; humicola sp; transmission electron microscopy

Biosynthesis of fluorescent Bi2S3 nanoparticles and their application as dual-functionSPECT-CT probe for animal imaging - Uddin, Imran; Ahmad, Absar; Siddiqui, Ejaz Ahmad; Rahaman, Sk. Hasanur; Gambhir, Sanjay (Current Topics In Medicinal Chemistry, 2016)
Bismuth sulphide (Bi2S3) is an excellent semiconductor and its nanoparticles have numerous significant applications including photovoltaic materials, photodiode arrays, bio-imaging, etc. Nevertheless, these nanoparticles when fabricated by chemical and physical routes tend to easily aggregate in colloidal solutions, are eco-unfriendly, cumbrous and very broad in size distribution. The aim of the present manuscript was to ecologically fabricate water dispersible, safe and stable Bi2S3 nanoparticles such that these may find use in animal imaging, diagnostics, cell labeling and other biomedical applications. Herein, we for the first time have biosynthesized highly fluorescent, natural protein capped Bi2S3 nanoparticles by subjecting the fungus Fusarium oxysporum to bismuth nitrate pentahydrate [Bi(NO3)(3).5H(2)O] alongwith sodium sulphite (Na2SO3) as precursor salts under ambient conditions of temperature, pressure and pH. The nanoparticles were completely characterized using recognized standard techniques. These natural protein capped Bi2S3 nanoparticles are quasi-spherical in shape with an average particle size of 15 nm, maintain long term stability and show semiconductor behavior having blue shift with a band gap of 3.04 eV. Semiconductor nanocrystals are fundamentally much more fluorescent than the toxic fluorescent chemical compounds (fluorophores) which are presently largely employed in imaging, immunohistochemistry, biochemistry, etc. Biologically fabricated fluorescent nanoparticles may replace organic fluorophores and aid in rapid development of biomedical nanotechnology. Thus, biodistribution study of the so-formed Bi2S3 nanoparticles in male Sprague Dawley rats was done by radiolabelling with Technitium-99m (Tc-99m) and clearance time from blood was calculated. The nanoparticles were then employed in SPECT-CT probe for animal imaging where these imparted iodine equivalent contrast.